Know your organism, know your data. (8th January 2017) - Mangel, Marc
Abstract : I review my career in marine science chronologically forward from the time that I decided to become a scientist to the present. Among other themes, I illustrate how much of my career was the result of recognizing good opportunities rather than specific plans, the role that search problems have played in my career, and the power of mathematical methods to allow us to find commonalities in systems appears totally different. I discuss in detail my involvement in the International Court of Justice between Australia and Japan concerning special permit whaling in the Antarctic and conclude with my current activities—showing that surprises can happen at any point in a career.